Sikap Masyarakat Indonesia Terhadap ODA (Official Development Assistance) Jepang Dan Dampaknya Terhadap Hubungan Jepang-Indonesia: Studi Kasus Proyek PLTA Koto Panjang - KASHIWABARA, KEIGO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In order to preserve their national interests Japan has been playing an important role in the international society, especially in the field of the development of developing countries, through its ODA (Official Development Assistance). Japanese ODA policy is very significant for its diplomatic strategy since economic power may be one of the biggest and most important diplomatic tools for the nation which cannot make any military contribution to the international community. Indonesia, which has the biggest economic potential in Southeast Asia, is the largest recipient of Japanese ODA. Japan has supported Indonesian's economic and social development in various fields by providing ODA for more than 50 years. Economics cooperation through ODA now functions as the core of the amicable bilateral relation s between the two countries. However, ODA alternatively has had some negative aspects on its recipients. Some of the ODA projects (called Mondai-ankens) have actually triggered various problems at project sites and have consequently afflicted the local people. The most well-known mondai-anken that aroused national discussion on ODA policy is Koto Panjang Hydropower Plant Project implemented in Riau Province, in 19 91-1997. The local community has been critical of Japanese ODA since the implementation of the project, which was done in a coercive manner under the Soeharto administration, caused costly damage to the local people such as poverty, scarcity of food, environmental destruction, and so on. Faced with these problems, the local people of Riau finally filed a suit in Japan against the Japanese government for compensation. Even though the case was dismissed on the grounds that it was regarded as an internal matter of Indonesia, as this sequence of events offered an incentive for a reform of Japan's ODA. After the social debate on ODA's transparency, public participation, and its effectiveness and efficiency, some new regulations and systems have been designed along with the amendment of Japan's ODA Charter. On the other hand, although the mondai-anken issue caused considerable damage to the recipient country people, and the local community filed a complaint to the donor country, this issue had no political impact to the bilateral relations between the two countries. Japan-Indonesia diplomatic relations have remained strong, never getting tense from the Koto Panjang Project issue. through the promotion of economic cooperation, Japan and Indonesia have not changed any policies concerning diplomatic relations between them. Economic cooperation still remains to be the principal pillar of the amicable relations between the two countries.